2017
DOI: 10.1167/iovs.15-18701
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by an RAR-γ Agonist of Collagen Degradation Mediated by Corneal Fibroblasts

Abstract: PURPOSE.To examine the role of retinoic acid receptor (RAR) isoforms in interleukin-1b (IL1b)-induced collagen degradation by corneal fibroblasts.METHODS. Primary rabbit corneal fibroblasts embedded in a three-dimensional collagen gel were incubated with or without all-trans retinoic acid (ATRA), the RAR-a agonist Am580, the RAR-b agonist AC55649, or the RAR-c agonist R667. Collagen degradation was determined by measurement of hydroxyproline produced in acid hydrolysates of culture supernatants. Matrix metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…For example, RA regulates the collagen composition and alters the balance between different collagen α chains in various cell types. 46 , 47 In the ventral angle, the collagen distribution in the extracelular matrix may be influenced by endogenous RA levels, and increased or decreased RA may have subsequent effects on aqueous outflow that are hidden by apoptosis. 48 Additional studies examining the different functions of RA are required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RA regulates the collagen composition and alters the balance between different collagen α chains in various cell types. 46 , 47 In the ventral angle, the collagen distribution in the extracelular matrix may be influenced by endogenous RA levels, and increased or decreased RA may have subsequent effects on aqueous outflow that are hidden by apoptosis. 48 Additional studies examining the different functions of RA are required.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of MMP-2 and MMP-9 gene expression (Rajashekhar, Shivanna, Kompella, Wang, & Srinivas, 2014;Xiao et al, 2012) RAR-β agonist AC55649 Primary rabbit corneal fibroblasts Incubation Reduction of MMP-2 and MMP-9 gene expression in a dose-dependent manner (Kimura et al, 2017) Female hormone 17β-estradiol Human corneal stromal cells Incubation Reduction of MMP-2 gene expression (Yin, Wan, Tian, Zhao, & Deng, 2018) Neuroprotectin D1 Herpes simplex virus (HSV)…”
Section: Alkali Burn Intraperitoneal Injectionmentioning
confidence: 99%
“…A previous report had proved that IL-1␤ inhibition represented a valuable alternative to inhibit vascular endothelial growth in the control of choroidal neovascularization caused by age-related macular degeneration (34). Moreover, IL-1␤ was shown to modulate various functions in corneal fibroblasts (5,16,18,21,26,27,44), and several studies also suggested that IL-1␤ was a key factor of early corneal neovascularization (CNV) (2,12,39,40). In suture-induced mouse CNV models, the vascular growth had been marked as the significantly upregulated expressions of both IL-1␣ and IL-1␤.…”
Section: Introductionmentioning
confidence: 99%